Effect of environmental performance and capital structure on financial performance: Evidence from mining sector companies listed on IDX - Sasiska Rani; Aida Rakhmawati; Wulandari Wulandari (New Applied Studies in Management, Economics & Accounting, 2024)
The benchmarks used to measure company performance use the triple bottom line concept, namely the company's financial success and resilience (profit), social welfare (people), and environmental health (planet). This research combines planetary and profit aspects by examining the influence of environmental performance (planet) and capital structure (profit) on financial performance in mining sector companies. Mining sector companies have a large environmental impact due to their business activities. A company's environmental performance is assessed by the Ministry of Environment and Forestry of the Republic of Indonesia through the Company Performance Rating Assessment Program (PROPER). The sample for this research consists of 12 mining sector companies listed on the Indonesian Stock Exchange in 2017-2021. The sampling technique used was purposive sampling. The research analysis technique uses multiple regression analysis which shows the results that environmental performance has a partial effect on financial performance, but capital structure has a partial effect on financial performance.